2021
DOI: 10.1021/acsomega.0c06140
|View full text |Cite
|
Sign up to set email alerts
|

Simple Regulation of the Self-Assembling Ability by Multimerization of Elastin-Derived Peptide (FPGVG)n Using Nitrilotriacetic Acid as a Building Block

Abstract: Elastin comprises hydrophobic repetitive sequences, such as Val-Pro-Gly-Val-Gly, which are thought to be important for the temperature-dependent reversible self-association (coacervation). Elastin and elastin-like peptides (ELPs), owing to their characteristics, are expected to be applied as base materials for the development of new molecular tools, such as drug-delivery system carrier and metal-scavenging agents. Recently, several studies have been reported on the dendritic or branching ELP analogues. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(35 citation statements)
references
References 62 publications
6
29
0
Order By: Relevance
“…The particle size measurement analyses indicated that the coacervation of AADAAC-F4 might follow a stepwise process in which sub-micron aggregates grow into micrometer-sized coacervates. Such a stepwise process is similar to that of the dendritic thermoresponsive ELP 55 and some strong coacervatable short ELPs that we reported earlier 49 51 . In addition, DLS measurements were carried out in the presence of Cd 2+ (Fig.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The particle size measurement analyses indicated that the coacervation of AADAAC-F4 might follow a stepwise process in which sub-micron aggregates grow into micrometer-sized coacervates. Such a stepwise process is similar to that of the dendritic thermoresponsive ELP 55 and some strong coacervatable short ELPs that we reported earlier 49 51 . In addition, DLS measurements were carried out in the presence of Cd 2+ (Fig.…”
Section: Resultssupporting
confidence: 83%
“…In addition, AADAAC-F4 can be readily recycled by simple treatment with an acidic solution and can be reused to collect Cd 2+ . Particle size distribution analysis indicated that AADAAC-F4 follows a stepwise self-association process involving the generation of sub-micron aggregates followed by coacervate maturation, which is similar to that observed for strong coacervatable short ELPs that we have previously reported 49 51 . Furthermore, microscopic analyses of AADAAC-F4 suggested that this peptide rapidly forms spherical particles several micrometers in diameter in the presence of Cd 2+ , implying that it can be easily separated from solution when used as a metal scavenging agent.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The distribution of the particle size in F5-FnY, F5-F1Y/F21Y, and F5-F1X (X = Trp, Ala, and Cha) solution was analyzed by dynamic light scattering (DLS) measurement using a Zetasizer nano ZS (Malvern Instruments Ltd., Worcestershire, UK) in a measurement cell ZEN0112 (Malvern Instruments Ltd.). [53] The peptide sample solutions were prepared at a concentration of 10 mg/mL in phosphate buffer (27.4 mM Na 2 HPO 4 , 17.8 mM NaH 2 PO 4 , pH 7.4) and filtered using the Millex-LG filter (Merck Millipore) before measurement. DLS analysis was performed by increasing the temperature at 10 C intervals from 0 to 40 C and 5 to 45 C. Measurement duration was selected automatically.…”
Section: Dynamic Light Scattering Analysismentioning
confidence: 99%
“…[51] Based on this repetitive sequence, we developed various thermoresponsive peptides, including nonlinear ELPs or combinations with other functional sequences. [52][53][54][55][56][57] Short-chain ELPs are beneficial as mass production by simple chemical synthesis is practically feasible without reconstructing the expression plasmids that are required for long-chain ELPs. Moreover, these short-chain ELPs allow the regulation of their physicochemical properties by replacing any amino acids with other amino acids, including D-amino acids or unnatural amino acids, in the chemical synthetic process.…”
Section: Introductionmentioning
confidence: 99%